Analysis of the Influence of Agricultural Natural Disaster on Farmers’ Technology Adoption Decision - Yu, Yawen; Wei, Jingzhou (Frontiers in Environmental Science, 2022)
Xinjiang is the main cotton producing area in China. However, its natural environment is special, and natural disasters frequently occur during the agricultural production process. Fortunately, the application of modern agricultural production technology provides a good tool for cotton farmers to reduce disaster losses. In order to analyze the impact of agricultural natural disasters on farmers' adoption of agricultural production technology, based on the survey data of 216 cotton farmers in the main cotton production areas, this paper uses a binary Logistic model to analyze the impact of disaster types and stages on cotton farmers' application of drip irrigation water-saving technology. The results show that: hail, drought and disease disasters have a significant impact on the application of drip irrigation water-saving technology, considering the damage to equipment and technology's control of disasters are the reasons behind; post-disaster remediation in the growth or maturity period also has a significant impact, which can reduce losses; market price risk for cotton also has a significant impact.